2003
DOI: 10.1007/s10038-003-0047-x
|View full text |Cite
|
Sign up to set email alerts
|

Genomic structure and alternative splicing of the insulin receptor tyrosine kinase substrate of 53-kDa protein

Abstract: Insulin receptor tyrosine kinase substrate of 53-kDa protein (IRSp53) is now known to be a key factor in cytoskeleton reorganization. The human IRSp53 was identified as a binding partner with DRPLA protein, a product of the gene responsible for a neurodegenerative disorder, dentatorubral pallidoluysian atrophy, as well as a binding partner with brain-specific angiogenesis inhibitor 1. Previous studies identified at least four isoforms (L-, M-, S-and T-forms) in human, where 511 amino acid residues from the N-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 19 publications
1
13
0
Order By: Relevance
“…S1B). Moreover, we confirmed the presence of three other murine IRSp53 family members (splice variants), described previously (Miyahara et al, 2003), in macrophages (supplementary material Fig. S1C).…”
Section: Requirement For Irsp53 For Csf-1-induced Cytoskeletal Reorgasupporting
confidence: 88%
“…S1B). Moreover, we confirmed the presence of three other murine IRSp53 family members (splice variants), described previously (Miyahara et al, 2003), in macrophages (supplementary material Fig. S1C).…”
Section: Requirement For Irsp53 For Csf-1-induced Cytoskeletal Reorgasupporting
confidence: 88%
“…IRSp53 is critical in Src-mediated transformation P-S Liu et al (that is, mIRSp53S, mIRSp53T and mIRSp58M) with different C-terminal amino-acid residues (Miyahara et al, 2003) were reported in murine cells. As insulin increased the phosphorylation of IRSp53S and IRSp53L, insulin-like growth factor I augmented the phosphorylation of IRSp53T (Okamura-Oho et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…IRSp53, also known as brain-specific angiogenesis inhibitor 1-associated protein 2 (Abbott et al, 1999;Oda et al, 1999), is a founding member of a newly discovered family of proteins, including missing-in-metastasis (MIM) and actin-bundling protein with brain-specific angiogenesis inhibitor 1-associated protein 2 homology (Scita et al, 2008). In addition to the originally identified 53-kDa protein IRSp53 (designated IRSp53S from now on), there are at least three other human isoforms (designated IRSp58M, IRSp53T and IRSp53L) have been identified whereas only three murine homologues (that is, mIRSp53S, mIRSp58M and mIRSp53T) have been detected (Miyahara et al, 2003). Interestingly, IRSp53S is suggested to be a candidate disease sensor of neurodegenerative polyglutamine (polyQ) expression (OkamuraOho et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Other cases of protein isoforms with or without a single amino acid residue During the course of the above experiments, we experienced other cases of inclusion or exclusion of 3 nt in a cloning process of GHRHR encoding the growth hormone releasing hormone receptor (Miki et al 1996) and also in the determination of exon-intron boundaries for BAIAP2 encoding IRSp53 Miyahara et al 2003). Literature surveys detected a few previous reports that clearly depicted isoforms with a subtle difference due to alternative splicing utilizing two acceptor sites separated by 3 nt (Manrow and Berger 1993;Condorelli et al 1994;Vogan et al 1996;Oberkofler et al 1997;Lin et al 2000; from PTMA to Dnmt1 in Table 1).…”
Section: Characterization Of Drpla Protein Isoformsmentioning
confidence: 99%